Barriers experienced by patients with multiple sclerosis in seeking care for lower urinary tract symptoms. Issue 4 (22nd August 2016) - Brucker, Benjamin M.; Nitti, Victor W.; Kalra, Sidhartha; Herbert, Joseph; Sadiq, Areeba; Utomo, Puspa; Aponte, Margarita M.
Abstract : AIM: The Actionable Bladder Symptom and Screening Tool (ABSST) is used to identify multiple sclerosis (MS) patients in possible need of evaluation for urinary symptoms. The primary objective of this study was to identify barriers experienced by MS patients in seeking evaluation for urinary symptoms. We also assessed the utility of ABSST tool in identifying patients that will follow up with urologic evaluation. METHODS: This was a prospective observational study where 100 patients with MS were enrolled from an MS center. Patients completed demographic information, questions to assess barriers to care, a short form of the ABSST, and incontinence questionnaires. An ABSST score> 3 met criteria for referral and evaluation. One year after enrollment, follow up calls assessed whether patients had seen a urinary specialist. RESULTS: The most common barriers to seeking care included "Doctor never referred" (16%) and "Doctor never asked" (13%). Thirty‐eight percent ( n = 8/21) of men stated "Doctor never referred" compared to 10% ( n = 8/79) of women ( P = 0.002). Twenty‐seven patients had an ABSST Score ≥3 and were more interested in seeing a specialist compared to those scoring <3 (88.9%, n = 24/27 vs. 26%, n = 19/73; P = <0.001). After 1 year, 70 patients were reached for follow up. A total of 57.9% ( n = 11/19) patients who followed up for evaluation screened positive on the ABSST. CONCLUSIONS: The ABSST is a valuable tool to identify MS patients with urinary symptoms who will likely follow up for genitourinary evaluation. However, other barriers beyond awareness exist and prevent patients from being evaluated.